2017
DOI: 10.1192/bjpo.bp.116.004325
|View full text |Cite
|
Sign up to set email alerts
|

Generalised joint hypermobility and neurodevelopmental traits in a non-clinical adult population

Abstract: BackgroundGeneralised joint hypermobility (GJH) is reportedly overrepresented among clinical cases of attention deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and developmental coordination disorder (DCD). It is unknown if these associations are dimensional and, therefore, also relevant among non-clinical populations.AimsTo investigate if GJH correlates with sub-syndromal neurodevelopmental symptoms in a normal population.MethodHakim-Grahame’s 5-part questionnaire (5PQ) on GJH, neuropsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In our study the 5PQ assigned 38.2% of the females and 19.3% of the males as GJH. This is similar to the prevalence rates reported in a large (n = 1039) Swedish study [13] also using the Swedish 5PQ as an assessment method for GJH. One study of female twins in the UK [5] reported the prevalence rate of GJH to be around 20%, although participants aged 20-30 years (similar age to our participants) had a prevalence rate (34%), closer to our findings.…”
Section: Prevalence Rates Of Gjh In Our Studysupporting
confidence: 88%
“…In our study the 5PQ assigned 38.2% of the females and 19.3% of the males as GJH. This is similar to the prevalence rates reported in a large (n = 1039) Swedish study [13] also using the Swedish 5PQ as an assessment method for GJH. One study of female twins in the UK [5] reported the prevalence rate of GJH to be around 20%, although participants aged 20-30 years (similar age to our participants) had a prevalence rate (34%), closer to our findings.…”
Section: Prevalence Rates Of Gjh In Our Studysupporting
confidence: 88%
“…Results showed that the rate of JH and autonomic symptoms were significantly higher among people with neurodevelopmental disorders than in the control group. More recently, Glans et al (31) explored the potential association between JH and autistic traits in the general population. One thousand thirty-nine Swedish adults responded to the Five-point questionnaire for JH (32), and others instruments assessing neurodevelopmental traits including the abridged version of the 50-item Autism Spectrum Quotient (33).…”
Section: Autism Joint Hypermobility (Jh) and Hypermobility-related Dmentioning
confidence: 99%
“…Nevertheless, these two clinical entities retain their association through into adulthood[ 26 , 36 ]. Interestingly, however, subclinical expression of neurodevelopmental (ADHD, ASD or DCD) traits in the general population are not strongly associated with hypermobility, suggesting that the expression of this association is limited to clinical populations[ 37 ].…”
Section: Resultsmentioning
confidence: 99%